STUDENTS SATISFACTION ON BILINGUAL PROGRAM IN MAKASSAR - Fansury, Andi Hamzah; Rampeng, Rampeng (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The objectives of the research were (1) to describe the students satisfaction on bilingual program at secondary school in Makassar and (2) to find out the students’ interest and motivation in learning English through Bilingual Program. The researcher applied mixed method namely triangulation mixed method design (QUAN-QUAL). The population of this research was the students of SMPN 12 Makassar in academic year 2015/2016. This research used purposive sampling. The sample of this research consisted of 40 students; 20 students from seventh grade and 20 students eight grade. In this research also, the researcher took 40 parents and 10 teachers as a sample. The research data were collected by questionnaire which was analyzed by descriptive statistic through SPSS version 16 for windows program. The result of data analysis shown that bilingual program improve English students skills, bilingual program makes the students mastery in English and learn it in their subjects matter (Mathematics, Science, and English). Bilingual also makes the students have better skills in learning English and, bilingual program has helped the students to develop as a person (students’ personality). The implementation of bilingual program at secondary school make the students are interested and motivated in learning English. From this fact, it points out the way of school and the governments to keep this program and make a policy to make this program keep going